PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA - Moh. Nurman Bagus Satrio (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
This study aims to determine whether or not there is a significant difference in Indonesian language learning outcomes between students taught by guided inquiry model with students taught by conventional learning to find the main idea of ​​a paragraph. This research was conducted at SMP Negeri 8 Jember in class VIII. The subject of this research is the students of class VIII A and class VIII B. This research type is quasi experiment with control-group design pretest-posttest design. Sampling technique with purposive sampling technique. Data collection techniques in the form of cognitive tests form a description and documentation. Data analysis technique using Mann Whitney U test. The result of research with significant level of 5% obtained there is difference of result of learning of mathematics which signifikan between student taught using guided inquiry model with student taught using conventional learning. Students who are taught using guided inquiry models have higher learning outcomes than students taught using conventional learning.